On the potential use of quarry waste material for CO2 sequestration. (December 2016) - Rigopoulos, Ioannis; Petallidou, Klito C.; Vasiliades, Michalis A.; Delimitis, Andreas; Ioannou, Ioannis; Efstathiou, Angelos M.; Kyratsi, Theodora
Graphical abstract: Highlights: Novel nanomaterials were produced via ball milling (BM) of quarry waste material. Various morphological and structural modifications occurred after the BM process. The optimum conditions are 20 h of BM with 50 wt% ethanol as process control agent. The BM process increased the CO2 uptake of mafic quarry wastes by a factor of ∼120. The presence of augite nanocrystals after BM is linked to the increased CO2 uptake. Abstract: The use of solid wastes rich in Ca 2+, Mg 2+ and Fe 2+ for the ex situ sequestration of CO2 could provide an economically and technologically viable option for the reduction of anthropogenic CO2 emissions. Here, we investigate for the first time the potential use of waste materials from mafic rock quarries as a feedstock for the sequestration of CO2 by ex situ mineral carbonation. The experimental procedure was performed on a waste material from a dolerite quarry operating in the Troodos ophiolite (Cyprus). The ball milling process was applied to this quarry waste in order to create nanomaterials with enhanced CO2 adsorption capacity. Through CO2 chemisorption followed by temperature-programmed desorption (CO2 -TPD) experiments, the optimum ball milling conditions were found (20 h of wet ball milling with 50 wt% ethanol as process control agent), leading to an enhancement of the CO2 -storage capacity of the waste material by a factor of ∼120. This enhancement of CO2 uptake is closely related to (i) the reduction of particle size to the nanoscale, (ii) the structural disordering of the constituent silicate minerals, and (iii) the presence of augite nanocrystals after ball milling. The experimental results suggest that waste materials from dolerite quarries may indeed be used as feedstock for the ex situ mineralization of CO2 . They also strongly demonstrate that ball milling is a very promising technique for optimizing the ex situ carbonation of this waste material; thus the proposed methodology could be a fundamental part of a future carbon sequestration strategy.